Re-defining the construct of market-orientation in the non-profit sector: an exploratory study - Macedo, Isabel Maria (2003)
In the context of an increasing competitive environment, in which organisations are compelled to manage their resources and capabilities in a more efficient and effective way, the concept of market orientation has been acknowledged as highly important in the marketing and management literature. However, the existing literature is mainly focused on the for-profit sector, and to our best knowledge little research has been undertaken in other organisational contexts, such as the non-profit sector. In this sense, the purpose of this study is to test a measure of market orientation already used in previous studies and to asses its psychometric properties in the context of non-profit organisations.